Analisis Persepsi Mahasiswa terhadap Efektivitas Penggunaan Apikasi GeoGebra dalam Pembelajaran Geometri - Nur Al Fariana; Nur Hardiani; Kristayulita Kristayulita (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2025)
The use of the GeoGebra application in geometry learning continues to grow; however, understanding of how students perceive its effectiveness remains limited. Therefore, this study aims to analyze students’ perceptions of the effectiveness of GeoGebra in geometry learning at the State Islamic University of Mataram. This research employed a descriptive qualitative approach involving second-semester Mathematics Education students. Semi-structured interviews and documentation were used as instruments to explore students’ experiences, assessments, and responses during GeoGebra-based learning. The data were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings indicate that, cognitively, GeoGebra supports students’ understanding of geometric concepts through interactive visualization, ease of exploration, and assistance in constructing and verifying concepts. Affectively, GeoGebra enhances students’ interest, comfort, and motivation to learn due to its engaging and user-friendly interface. These findings suggest that GeoGebra is effective in fostering more interactive and meaningful geometry learning. The study further implies the importance of integrating GeoGebra into higher education geometry courses as an effort to strengthen conceptual understanding and promote students’ learning motivation.